Graduate Programs in Green Growth and Sustainable Development: A Comparative Approach - Fairlie Reinoso, Alan (2017)
Since the concern about the negative impacts of the current economic modelin the scarcity of natural resources and their conservation, it comes the need toconfront them and create, from academia, some research areas that include thesenew features and development trends. In this paper, an overview of the conceptualaspects of the main proposals for the transition to sustainable development isperformed, such as the Green Growth, Bio-Commerce, Bio-Economy, amongothers. Then, it is identified and analyzed a group of graduate programs developedon the sustainable development. Finally, a comparative balance, based on the offerof the Master of Bio and Sustainable Development.